Red blood cell Thomsen‐Friedenreich antigen expression and galectin‐3 plasma concentrations in Streptococcus pneumoniae–associated hemolytic uremic syndrome and hemolytic anemia. Issue 6 (30th December 2014) - Burin des Roziers, Nicolas; Chadebech, Philippe; Bodivit, Gwellaouen; Guinchard, Emmanuelle; Bruneel, Arnaud; Dupré, Thierry; Chevret, Laurent; Jugie, Myriam; Gallon, Philippe; Bierling, Philippe; Noizat‐Pirenne, France
Abstract : Background: Pneumococcal hemolytic uremic syndrome (P‐HUS) is a rare but severe complication of invasive pneumococcal disease (IPD) in young children. Consensual biologic diagnosis criteria are currently lacking. Study Design and Methods: A prospective study was conducted on 10 children with culture‐confirmed IPD. Five presented with full‐blown P‐HUS, three had an incomplete form with hemolytic anemia and mild or no uremia (P‐HA), and two had neither HUS nor HA. Thomsen‐Friedenreich (T), Th, and Tk cryptantigens and sialic acid expression were determined on red blood cells (RBCs) with peanut (PNA), Glycine soja (SBA), Bandeiraea simplicifolia II, and Maackia amurensis lectins. Plasma concentrations of the major endogenous T‐antigen–binding protein, galectin‐3 (Gal‐3), were analyzed. Results: We found that RBCs strongly reacted with PNA and SBA lectins in all P‐HUS and P‐HA patients. Three P‐HUS and three P‐HA patients showed also concomitant Tk activation. Direct antiglobulin test (DAT) was positive in three P‐HUS (one with anti‐C3d and two with anti‐IgG) and two P‐HA patients (one with anti‐C3d and one with anti‐IgG). RBCs derived from the two uncomplicated IPD patients reacted with PNA but not with SBA lectin. Gal‐3 plasma concentrations were increased in all P‐HUS patients. Conclusions: The results indicate high levels of neuraminidase activity and desialylation in both P‐HUS and P‐HA patients. T‐antigen activation is more sensitive than DAT for P‐HUS diagnosis. Combining PNA and SBA lectins is needed to improve the specificity of T‐antigen activation. High concentrations of Gal‐3 in P‐HUS patients suggest that Gal‐3 may contribute to the pathogenesis of P‐HUS.